Răspuns :
Răspuns:
Explicație pas cu pas:
a / b = 3/2 ⇒ a / 3 = b / 2 = k ⇒ a = 3 k si b = 2 k
( 4 a + 2 b ) / ( 3 a + b ) = 16 / 11
= ( 4 × 3 k + 2 × 2 k ) / ( 3 × 3 k + 2 k ) =
= 16 k / 11 k =
= 16/11
________________________________
sau:
a / b = 3/2 ⇒ 2 a = 3 b ⇒ a = 3 b / 2
( 4 a + 2 b ) / ( 3 a + b ) =
= ( 4 × 3 b/2 + 2 b ) / ( 3 × 3 b/2 + b ) =
= ( 6 b + 2 b ) / ( 9 b / 2 + 2 b / 2) =
= 8 b : ( 11 b / 2 ) =
= 8 b × 2 / 11 b =
= 16 / 11
Răspuns:
(4a+2b)/(3a+b)= (4 .3+2 .2)/(3 .3+2)=14/11
Explicație pas cu pas: